第7章习题答æ&iexcl

第7章习题答æ&iexcl

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 7( ª ½ Š 1 f x =2| x| +1 á + F x t å D ± iÖ Ð * ª ¿ ò P 2P D ± iÖ Ð * ª ¿ ò 1 { 〈x y〉 | x y∈N x+y< 10} 23 { 〈x y〉 | x y∈R y=x2} 33 { 〈x y〉 | x y∈R y2=x} 13 3PÖ D ± i Ð * ªò ¿ 2(Š ª ½ 3@ 7 D ± k 3 1 { 〈1,〈2,3〉 〉 ,〈2,〈3,4〉 〉 ,〈3,〈1,4〉 〉 ,〈4,〈1,4〉 〉 } 2 { 〈1,〈2,3〉 〉 ,〈2,〈3,4〉 〉 ,〈3,〈3,2〉 〉 } 3 { 〈1,〈2,3〉 〉 ,〈2,〈3,4〉 〉 ,〈1,〈2,4〉 〉 } 4 { 〈1,〈2,3〉 〉 ,〈2,〈2,3〉 〉 ,〈3,〈2,3〉 〉 } (1) (2) (4)( * ª ½ Š (1)( ª ½ Š {1,2,3,4}, { 〈2,3〉 ,〈3,4〉 ,〈1,4〉 } (2)( ª Š ½ {1,2,3}, { 〈2,3〉 ,〈3,4〉 ,〈3,2〉 } (4)( ª Š ½ {1,2,3}, { 〈2,3〉 } 4 f gŠ* ½ (ª f ⊆ g dom g =dom f ½ ª( Š f≠ g f ⊆ g dom g =dom f½ ª( Š f½ ª( м i ª∆ * D ± û 〈x1,y1〉∈ g 〈x1,y1〉∉ f f ⊆ g 〈x1,y2〉∈ g • g¿ ª¨ *→ * ª ¾ D ë 〈x1,y2〉∈ f X 6 X={0 1 2 } X Šª ½ -* ( 2 13 f x =f x 23 f 2 x =x 33 f 3 x =x 1 10Š* ½ -ª ( f 1 x = { 〈0,0〉 ,〈1,0〉 ,〈2,0〉 } f 2 x = { 〈0,1〉 ,〈1,1〉 ,〈2,1〉 } f 3 x = { 〈0,2〉 ,〈1,2〉 ,〈2,2〉 } f 4 x = { 〈0,1〉 ,〈1,1〉 ,〈2,2〉 } f 5 x = { 〈0,2〉 ,〈1,1〉 ,〈2,2〉 } f 6 x = { 〈0,0〉 ,〈1,0〉 ,〈2,2〉 } f 7 x = { 〈0,0〉 ,〈1,2〉 ,〈2,2〉 } f 8 x = { 〈0,0〉 ,〈1,1〉 ,〈2,0〉 } f 9 x = { 〈0,0〉 ,〈1,1〉 ,〈2,1〉 } f 10 x = { 〈0,0〉 ,〈1,1〉 ,〈2,2〉 } 2 4Š* ½ (ª f 1 x = { 〈0,0〉 ,〈1,1〉 ,〈2,2〉 } f 2 x = { 〈0,0〉 ,〈1,2〉 ,〈2,1〉 } f 3 x = { 〈0,2〉 ,〈1,1〉 ,〈2,0〉 } f 4 x = { 〈0,1〉 ,〈1,0〉 ,〈2,2〉 } 3 3Š* ½ (ª f 1 x = { 〈0,0〉 ,〈1,1〉 ,〈2,2〉 } f=g x1∈dom g dom f y2 f=g f 2 x = { 〈0,1〉 ,〈1,2〉 ,〈2,0〉 } f 3 x = { 〈0,2〉 ,〈1,0〉 ,〈2,1〉 } 8 f,g,h N → N , Nx ª ½ * X • f(n) n 1, g(n) 2n, 0 h(n) = 1 3 3 n n f f3 f g3 g h3 h g 3 (f g) h3 ( f f ) ( x ) = f ( f ( x ) ) = f ( x + 1) = x + 1 + 1 = x + 2 ( f g ) ( x) = f ( g ( x) ) = f ( 2x) = 2x +1 x x 0 = 2 x x g ( 0) ( g h)( x) = g (h( x)) = g (1) ( h g) ( x ) = h ( g ( x ) ) = h ( 2 x ) = 0 ( f g )(0) ( f g ) h ( x) = ( f g )(h( x)) = ( f g )(1) 14txF+ 13 23 33 43 53 x x 1 = 3 x x åá f Z+→R f n =log10n Z+ f R+→R f n =log10n R+ f R→R f x =2x-15 f R+× R→R+ f x y =xy R+ f R+× R→R f x y =xy R+ 1½ X • xª 2 3 g f 3 ½ •* Xx ª g f3 X → Z 4 5 15 g f ò Ô h 3 23 f3 g3 ½ •* (x ª 3 3 f X→ Y g Y →Z x1 x2∈X g f3 x1 =g f3 x2 g 3½ x (•* ª f 3x (½ •ª g3 f3 x1 f3 x1 = f3 x2 33 =g3 f3 x2 x1=x2 g f 3 (u•½ª g f\ ï 3 13 3 g f 3 Øw * ª ½ • g 3 Øw ª ½ • 3 3 f X →Y g Y →Z g f3 X →Z z∈Z g f 3 Øw ª ½ • ª ½ • Øw x∈X g f3 x3 =z3 g3 f3 x3 =z3 3 3 fu (•½ª* y3 3 f3 x3 =y3 f3 x3 =y 3 3 (•½ª* u g 3 (•½ª u 19\ ¿ ï A B( u * ª ½ • A →Bu ª ½ • ( 2 A=Z B=N 17 4 A=N× N B=N x∈N 2x 2 f x = − 2 x − 1 x ∈ Z − N 34 213 8.5 2+3m+n]/2 g3 f3 x3 =z 3 g3 y3 =z3 f m n =[ m+n 24 ½ *Ø ªω • A′ 1½ *w Ø ª• f A →B ½ *w Ø ª• A′ f| A′ A½ *w Ø ª• f| A′ A ′→ B x1 x2∈A ′ AØ ½ w *• ª x1 =f| A ′ x2 f| A′ ½ w ¬ ª• f ت• ½ w * f| A′ x1 x2∈A f x1 =f x2Ø• ½ w ª x1 =f x1 Ø• ½ w * ª f| A′ x2 =f x2 f| A′ x1=x2 ...
View Full Document

Ask a homework question - tutors are online